Study of Processing of Municipal Solid Waste Landfill Leachate: Enhancing Chemical Treatment of Municipal Solid Waste Landfill Leachate with Natural Accelerators (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The release of leachate poses a serious risk to both surface water and groundwater from MSWdumps. Leachate is any liquid that percolates through a landfill and collects the solids and liquids thathave been stored there. When garbage has moisture, it attracts rainwater, which then seeps into thelandfill and forms leachate. In this paper, we present the findings of an analysis of an aerobic treatmentprocess applied to leachate from Ghazipur (Delhi) landfill, by way of coagulation flocculation theory, withthe aid of coagulant and accelerator substances to speed up and improve coagulation and flocculationperformance.The primary objective of this research was to utilise a naturally occurring, low-cost material as anaccelerator addition to improve the chemical treatment process using Alum coagulant, with theaccelerator ingredients being Perlite and Bentonite. The accelerator chemicals, including Alum at aconstant concentration of 90 mgl, significantly improved the efficacy of the chemical therapy. We foundthat the performance of perlite effluent was superior than that of bentonite. At a concentration of 40 mgl,the removal ratios for Perlite were 86.7 for conductivity, 87.4 for turbidity, 89.9 for biological oxygendemand (BOD), and 92.8 for chemical oxygen demand (COD). For Bentonite, these values were 83.5for conductivity, 85.0 for turbidity, 86.5 for BOD, and 85.0 for BOD.